Disposition and metabolism of 2′,2′”-Dithiobisbenzanilide in rodents following intravenous and oral administration and dermal application - C. Edwin Garner; Christopher J. Wegerski; Melanie Doyle-Eisele; Jacob D. McDonald; J. Michael Sanders; Benjamin C. Moeller; Suramya Waidyanatha (Toxicology Reports, 2020)
2′,2′′′-Dithiobisbenzanilide (DTBBA) is a high-production-volume chemical used as a peptizing agent for rubber. The disposition and metabolism of [14C]DTBBA were determined in male and female rats and mice following oral (4, 40, or 400 mg/kg) and intravenous (IV) (4 mg/kg) administration and dermal application (0.4 or 4 mg/kg). [14C]DTBBA was well absorbed following oral administration (> 60%) and dermal application (∼40–50%) in rats and mice. Following oral administration, the majority of radioactivity was excreted in urine (29 − 70%) and feces (16 − 45%). Unlike rats, mice excreted ∼1-5% of the dose as exhaled CO2. The residual radioactivity in tissues was <1% in both species and sexes. The pattern of disposition following IV administration in male rats was similar to that following oral. When [14C]DTBBA was administered via IV to rats, a significant portion of the dose was recovered in bile (∼13%) suggesting that at least a portion of the dose recovered in feces following oral administration was likely the absorbed dose. The profiles of urine from rats and mice were similar and consisted of four major metabolites and three minor metabolites. The predominant metabolite in urine was the S-glucuronide of the thiol/sulfide cleavage product N-(2-mercaptophenyl)benzamide, which accounted for more than 50% of radioactivity in the radiochromatogram.